MR-Guided Radiotherapy for Liver Malignancies - Boldrini, Luca; Corradini, Stefanie; Gani, Cihan; Henke, Lauren; Hosni, Ali; Romano, Angela; Dawson, Laura (Frontiers in Oncology, 2021)
MR guided radiotherapy represents one of the most promising recent technological innovations in the field. The possibility to better visualize therapy volumes, coupled with the innovative online adaptive radiotherapy and motion management approaches paves the way to more efficient treatment delivery and may be translated in better clinical outcomes both in terms of response and reduced toxicity. Aim of this review is to present the existing evidence about MRgRT applications for liver malignancies, discussing the potential clinical advantages and the current pitfalls of this new technology.